2017
DOI: 10.1177/1755088217748970
|View full text |Cite
|
Sign up to set email alerts
|

Trauma as counter-revolutionary colonisation: Narratives from (post)revolutionary Egypt

Abstract: We argue that multiple levels of trauma were present in Egypt before, during and after the 2011 revolution. Individual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The study is situated within the literature on politics of disappointment (Greenberg 2014;Gould 2009) in post-revolution Egypt (Matthies-Boon andHead 2018;Allam 2018). The focus in this tradition is on how excessive repression distorts the way individuals understand the society and authority and deepens their existential meaninglessness and desperation.…”
Section: Politics Of Depoliticizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study is situated within the literature on politics of disappointment (Greenberg 2014;Gould 2009) in post-revolution Egypt (Matthies-Boon andHead 2018;Allam 2018). The focus in this tradition is on how excessive repression distorts the way individuals understand the society and authority and deepens their existential meaninglessness and desperation.…”
Section: Politics Of Depoliticizationmentioning
confidence: 99%
“…Since 2013, a body of literature examining the effect of repression from the perspective of individual activists has emerged. Part of this literature focuses on the role of emotions to explain processes of mobilization, demobilization, depoliticization and social trauma (Kienle and Sika 2015, Sika 2016a, 2016band 2017Allam 2018;Matthies-Boon and Head 2018). However, this literature remains largely focused on the actors who have mobilized in revolutionary process and in opposition to the regime, and who have been subjected to direct repression as a consequence, including imprisonment.…”
Section: Introductionmentioning
confidence: 99%
“…The passing of memories, be they actually lived memories or parts of a constructed collective memory, is a process that produces certain states of mind and political opinions that can influence the further course of history (Lerner, 2019: 550). Matthies-Boon and Head (2018) found that authoritarian governments are not only creating individual trauma such as PTSD, but also social and political trauma: “The social trauma occurring in repressive authoritarian societies […] occurs due to the restriction of communicative spaces and the strategic deconstruction of potential forms of social and collective flourishing” (2018: 262). Their insights on post-revolutionary Egypt are comparable with the situation inside Eritrea, where mutual mistrust due to intensive surveillance has severely damaged the social fabric.…”
Section: Postmemory the Government Of Eritrea And The Legacy Of The Martyrsmentioning
confidence: 99%
“…He describes unflinchingly the nature of Israel's control of the Gaza Strip and its consequences for its occupied and besieged inhabitants. We might think of this as “the colonization of the lifeworld through multi‐layered forms of traumatic betrayal” which “when left unaddressed may become expressed through political apathy, social alienation and personal meaninglessness” (Matthies‐Boon & Head, 2018). While the research data confirm the prevalence of the symptomatology of clinical trauma, the capacity of Gaza's young to initiate and sustain a form of collective protest seen in the Great March of Return suggests a society that has not succumbed to the dissolution that siege is designed to achieve .…”
mentioning
confidence: 99%
“… See Matthies‐Boon and Head (2018) for a discussion of what they call “political trauma” – “a systematic attempt to break communicative, social and political relations” ‐ inflicted upon Egyptian society by the military and the Muslim Brotherhood before, during and after the revolution of 2011. The authors offer a critique of individualist and intrapsychic models of trauma that are highly relevant to engaging with the Palestinian experience in Gaza, and indeed all of occupied Palestine. …”
mentioning
confidence: 99%